2014
DOI: 10.1088/0957-4484/25/43/435601
|View full text |Cite
|
Sign up to set email alerts
|

Study of thermal stability of (3-aminopropyl)trimethoxy silane-grafted titanate nanotubes for application as nanofillers in polymers

Abstract: Protonated titanate nanotubes (TiNT-H) were surface-modified with (3-aminopropyl)trimethoxy silane (APTMS) by novel method suitable for syntheses of large amounts of materials with low costs. Usage of prepared nanotubes for polymer reinforcement was studied. Since the thermal stability of nanofiller was important to preserve their functional properties, stability was studied by in situ high temperature measurements. The most thermally stable nanotubes, silanized for 20 min, were used for preparation of epoxy-b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…But these properties were inferior to that of Nafion. Hence, to improve the overall properties of the SPEEK, nano inorganic fillers like TiO 2 [15], ZrO 2 [16] and SiO 2 [17], SnO 2 [18], WO 3 [19] were incorporated into the SPEEK membrane. From these research studies it was revealed that the addition of nano particles increases hydrophilic nature and provides a preferential path for protons transfer through water molecules (Grotthuss mechanism).…”
Section: Introductionmentioning
confidence: 99%
“…But these properties were inferior to that of Nafion. Hence, to improve the overall properties of the SPEEK, nano inorganic fillers like TiO 2 [15], ZrO 2 [16] and SiO 2 [17], SnO 2 [18], WO 3 [19] were incorporated into the SPEEK membrane. From these research studies it was revealed that the addition of nano particles increases hydrophilic nature and provides a preferential path for protons transfer through water molecules (Grotthuss mechanism).…”
Section: Introductionmentioning
confidence: 99%
“…photocatalysis 4,5 and photovoltaics, 6 but also because of the intrinsic advantages of the method, simplicity and cost efficiency. 7 Surface functionalization of nanoparticles with organic molecules such as silane coupling agents, [8][9][10][11][12] brings additional properties and better dispersion in organic solvents and polymers. [12][13][14][15] The effect of the synthesis conditions on the morphology of TiO2 nanoparticles has been the focus of numerous works.…”
Section: Introductionmentioning
confidence: 99%
“…7 Surface functionalization of nanoparticles with organic molecules such as silane coupling agents, [8][9][10][11][12] brings additional properties and better dispersion in organic solvents and polymers. [12][13][14][15] The effect of the synthesis conditions on the morphology of TiO2 nanoparticles has been the focus of numerous works. Dinh et al studied solvothermal synthesis of anatase TiO2 in ethanol reporting different shapes such as rhombic, truncated rhombic, spherical, and dog-bone, by tuning the oleic acid and oleylamine surfactants molar ratio.…”
Section: Introductionmentioning
confidence: 99%
“…Sodium titanate nanotubes (NaTiNTs), as one-dimensional TiO 2 related nanomaterials, exhibit some distinct advantages, including high specific surface area, high density of surface -OH groups, ion-exchange and semiconducting properties 27 . NaTiNTs have a structure similar to a rolled-up carpet, in which sodium plays an important role in the formation of the nanotubular structure.…”
Section: Introductionmentioning
confidence: 99%